Developing physics lesson plan for SMA by using problem based learning model with saintific approach - Yardani Adi Cosra; Yulkifli Yulkifli; Ratnawulan Ratnawulan (Fakultas Ilmu Pendidikan UNP)
The standard of content and the standard of process of curriculum 2013 require scientific learning, a scientific approach involving models that emphasize the problem. The purpose of this research to develope physics lesson plan for SMA by using Problem Based Learning with saintific approach with criteria valid, practis, efective. The kind of research is used research and development. The model development is used ADDIE model, it consist of analysis, design, development, implementation, evalution. The test of validity were done through validity sheet of learning device, practicality testing through observation sheet, questionnaire response of the teachers and the students, affectivity testing were obtained from the assessment of knowledge, attitude, characters, skills. Thisresearch was conducted at grade X of SMAN 4 Kerinci which consists of 35 students and two physics teachers as respondents.This research produces physics lesson plan used problem based learning model with saintific approach material Temperature, Heat and Transfer that valid, practis, efective.